DETERMINATION OF OPTIMAL PORTFOLIO BY USING SHARPE RATIO FOR QATAR STOCK MARKET (PERIOD JAN2013-JAN2023) - Fadilla, Rizaldi
In making investment decisions, portfolio management is an important aspect that aims to optimize results while managing risk. Sharpe ratio and covariance matrix will be used in writing this time. The Sharpe ratio, developed by William F. Sharpe, measures the risk-adjusted return of an investment strategy, while the covariance matrix provides insights into the relationships and diversification benefits among assets within a portfolio. The Sharpe ratio serves as a valuable tool for investors seeking to compare and evaluate the risk-reward profile of different portfolios. It calculates the excess return of a portfolio per unit of risk taken, typically using a risk-free rate as the benchmark. Higher sharpe ratios indicate better risk-adjusted performance, as they reflect a greater return per unit of volatility. The covariance matrix, on the other hand, quantifies the interdependencies between the returns of different assets in a portfolio. By examining the historical relationships and correlations among asset returns, investors can identify potential diversification opportunities. The findings of this comparison study are evidenced by the increase in the sharpe ratio from 0.47 to 0.73 and the expected return from 8.77% to 13.09% and the decrease in risk (standard deviation) from 17.99% to 17.52% and optimal weight with maximum sharpe ratio which is diversified into several industrial sectors. Comparison with the Qatar Stock Index sharpe ratio (-0.047) also shows risk investment in the Qatar stock market is better because above it and T-Bill Qatar 10year yield is 3.07%.